The relationship between parental autonomy support, teacher autonomy support, peer support, and university students’ academic engagement: the mediating roles of basic psychological needs and autonomous motivation - Li, Yan; Sueb, Rosilawati; Said Hashim, Khadijah (Frontiers in Psychology, 2025)
ObjectiveThis study, based on Ecological Systems Theory and Self-Determination Theory, explores the relationships between parental autonomy support, teacher autonomy support, peer support, and university students’ academic engagement from a positive psychology perspective, as well as the mediating roles of basic psychological needs and autonomous motivation.MethodsA questionnaire survey was conducted with 416 university students from four universities in Guangxi, using the Academic Engagement Scale, Parental Autonomy Support Scale, Teacher Autonomy Support Scale, Peer Support Scale, Basic Psychological Needs Scale, and Learning Motivation Scale.Results(1) Teacher autonomy support was significantly positively associated with university students’ academic engagement; peer support was significantly negatively associated with academic engagement; parental autonomy support was not significantly associated with academic engagement. (2) Basic psychological needs significantly mediated the relationships between parental autonomy support, teacher autonomy support, peer support, and academic engagement. (3) Autonomous motivation significantly mediated the relationships between parental autonomy support, teacher autonomy support, and academic engagement, while it was not significantly associated with the relationship between peer support and academic engagement. (4) Basic psychological needs and autonomous motivation played a chain-mediating role in the relationships between parental autonomy support, teacher autonomy support, peer support, and academic engagement.ConclusionTeacher, parental, and peer support influence university students’ academic engagement through different pathways, with basic psychological needs and autonomous motivation serving as important “bridging” factors.